2018
DOI: 10.1364/boe.9.004879
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a transparent cranial implant as a permanent window for cerebral blood flow imaging

Abstract: Laser speckle imaging (LSI) of mouse cerebral blood flow was compared through a transparent nanocrystalline yttria-stabilized zirconia (nc-YSZ) cranial implant over time (at days 0, 14, and 28, n = 3 mice), and vs. LSI through native skull (at day 60, n = 1 mouse). The average sharpness of imaged vessels was found to remain stable, with relative change in sharpness under 7.69% ± 1.2% over 28 days. Through-implant images of vessels at day 60 appeared sharper and smaller on average, with microvessels clearly vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…Therefore, brain imaging has been predominantly demonstrated in rodent open-skull and thinned skull models. Likewise, in our own prior studies we have found that optical imaging through the intact skull of mice diminishes detection of the intrinsic optical signals [24][25][26][27] . Moreover, the optical properties of the inhomogeneous cranial bone overlap with those of brain tissue and jointly these factors decrease the accuracy and reliability of the data.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Therefore, brain imaging has been predominantly demonstrated in rodent open-skull and thinned skull models. Likewise, in our own prior studies we have found that optical imaging through the intact skull of mice diminishes detection of the intrinsic optical signals [24][25][26][27] . Moreover, the optical properties of the inhomogeneous cranial bone overlap with those of brain tissue and jointly these factors decrease the accuracy and reliability of the data.…”
Section: Introductionmentioning
confidence: 66%
“…Glass and PDMS windows are powerful research techniques, but are not appropriate for human application as permanent cranial implants for patients. Like skull thinning and polishing techniques, glass-based windows compromise protection for the brain due to the extremely low fracture toughness of typical glasses (KIC = 0.7-0.9 MPa m1/2) 36 which increases potential for catastrophic failure by fracture, while the effect of skull optical clearing agents for long-term use on human skull is still unknown 24 . A number of biomedical considerations including biocompatibility, mechanical strength, and ageing should be examined in order to create an optical window for eventual clinical application 24 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When MSRI has been applied through the intact skull, only skull regions and not individual microvessels are visible . Likewise, in our own prior studies we have found that imaging through intact skull with LSI limits the size of vessels that can be detected, and precludes imaging of the microcirculation . Moreover, the absorption and reflectance features of the inhomogeneous cranial bone overlap with those of brain tissue, and the skull also has its own vessels.…”
Section: Introductionmentioning
confidence: 87%